O Simbolismo das Cores no Livro de José de Arimateia - Pedro Chambel (Medievalista)
The Book of Joseph of Arimathea is a medieval text probably translated to Portuguese in the XIIIth century, wrote as the first part of the Post-Vulgate cycle. The book is a narrative about the Holy Grail, the chalice that was supposed to contain the blood shed by Jesus Christ while crucified, collected by Joseph of Arimathea; and also the adventures of the characters that interact with the grail while it was taken from Jerusalem to Great Britain. In this text there are references to several colors -white, red, green, black, blue and gold – which have symbolic meanings, that must be interpreted and taken into account on the analysis and comprehension of a narrative with a strong allegoric-symbolic content. Therefore, I intend to add a contribution to the study of the colors symbolism on Portuguese medieval texts, as an approach to their analysis, and give rise to a comparison of the meanings proposed by this study both with those of other texts written around the same time, and with other medieval forms of expression.